THE RICHNESS OF TAFSIR AL-QUR’AN: METHODS IN INTERPRETING THE VERSES OF THE QUR'AN - Wahyudi, Ahmad Ilham; Haq, Muhammad Rizqi Manarul; Said, Hasani Ahmad (HUNAFA Jurnal Studia Islamika, 2023)
This research intends to explore various treasures of Al-Qur'an interpretation related to the method of interpreting the verses of the Qur'an. This research is a qualitative research in the form of library research (Library Research). The primary data sources used are the Al-Qur'an and the book of Tafsir related to the methodology of al-Qur'an interpretation by al-Farmawi and M. Quraish Shihab. While the secondary data sources used are various scientific literature relevant to the core object of this research. This research includes conceptual research with a philosophical-normative approach. While the nature of this research approach is descriptive-analytic and prescriptive. The results of this study indicate that there are four methods of interpreting the verses of the Koran, namely the tahlîli method, the maudhû'i method, the ijâmlî method, and the muqâran method. In the development of interpretation, there are new methods of interpretation in the treasury of the science of exegesis as initiated by contemporary interpreters, namely the semi-maudhîli tahlîli interpretation method, the semi-tahlîli maudhû'i interpretation method, and the semi-tahlili ijâmlî interpretation method.